Knowledge and Practice of General Dentists Regarding the COVID-19 in Zanjan, Iran - B Nazemi Salman; L Eftekhar; SH Arsang Jang; SS Taheri; F Jafari (Islamic Azad University, 2023)
Background and Aim: Severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) that caused the coronavirus disease-2019 (COVID-19) pandemic is transmitted through close contact via respiratory droplets when an infected patient sneezes, coughs, or talks. Due to close contact with patients, dentists are at higher risk of COVID-19. The aim of this study was to evaluate the knowledge and practice of general dentists in Zanjan regarding the COVID-19.   Materials and Methods: This cross-sectional study was conducted on 107 general dentists working in Zanjan city in September 2021, simultaneous with the fifth wave of the COVID-19, who were selected by census sampling. A researcher-designed questionnaire was used to assess the knowledge and practice after assessing its reliability and validity. The effect of age, gender, work experience, and place of work on knowledge and practice of dentists was analyzed by one-way ANOVA, independent sample t-test, and Pearson's correlation test (alpha=0.05). Results: Of all, 89 questionnaires were returned. The mean age of the participants was 35.9 years, and 77.5% of dentists acquired their knowledge about COVID-19 pandemic through the social networks. The mean knowledge and practice scores of dentists were 70.73±10.67 and 58.51±12.81, respectively (out of 100). Dentists with 5 to 15 years of work experience had the highest level of knowledge (P=0.018). The practice score significantly increased with age (P=0.003). Also, dentists with more than 15 years of work experience acquired higher practice scores (P=0.000) Conclusion: Dentists' knowledge and practice regarding COVID-19 and its treatment was moderate to high (optimal). However, their knowledge and practice were still far from the ideal level, indicating the need for educational planning to enhance their knowledge and improve their practice to deal with COVID-19.